AB0443 Selective Immunomodulators of FC-Gamma Receptors (SIFS) to Inhibit Autoantibody-Mediated Pathology. (9th June 2015) - Bosques, C.J.; Lansing, J.; Ortiz, D.; Rutitzky, L.; Washburn, N.; Bhatnagar, N.; Kurtagic, E.; Choudhury, A.; Prod'homme, T.; Schultes, B.; Roy, S.; Kaundinya, G.V.; et al.
Abstract : Background: Interaction of autoantibodies and immune complexes with Fcγ-receptors on leukocytes can lead to detrimental inflammatory events in autoimmune diseases including inflammatory synovitis. Modulation of Fcγ-receptor-mediated leukocyte activation could serve as an attractive strategy to limit acute exacerbations and recurrent disease symptoms in rheumatoid arthritis and multiple disease settings. Objectives: To develop best-in-class modulators of Fcγ-receptors and assess their activity in antibody-mediated pathogenic mechanisms active in autoimmune diseases. Methods: We designed a panel of novel recombinant multimeric-Fc drug candidates to modulate the activity of low affinity Fcγ-receptors. A comprehensive panel of physicochemical and pharmacological assays including in-vivo models of Immune Thrombocytopenic Purpura (ITP) and synovitis (Collagen Antibody-Induced Arthritis; CAIA) was used to select the candidate with optimal drug properties. Results: An optimal multimeric-Fc drug candidate was selected for development based on its attractive physicochemical and biological properties. This candidate demonstrated more than 40 fold higher potency than Intravenous Immunoglobulins (IVIg) in multiple in-vivo models of autoimmune diseases and more than 100 fold potency in different assays of immune cell activation. Conclusions: Selective Immunomodulators of Fcγ-receptors (SIFs) are effective inhibitors of various antibody-mediated pathogenic mechanisms. These novel agents may prove to have therapeutic value in the treatment of autoimmune diseases. Disclosure of Interest: None declared